Замечания об Lp—Lq оценках решений уравнения Клейна — Гордона - Марковский А.И. (Український математичний журнал, 1992)
Усуваються недоліки в доведеннях ряду оцінок, установлених раніше в статті Маршалла, Штрауса і Вайнгера, присвяченій Lp—Lq оцінкам розв’язків рівняння Клейна — Гордона. We clarify some difficulties in the proofs of estimates, which were established earlier, in the paper by Marshall, Straus and Wainger devoted to the Lp —Lq estimates of solutions to the Klein-Gordon equation.